Educational inclusion from the perspective of the academics responsible for teacher training at the Universidad Católica del Maule – Chile - Cornejo Espejo, Juan (2019)
The article, the results of a study carried out with academic teacher educators of the Universidad Católica del Maule, to which a survey was applied based on a Likert scale, seeks to reveal their opinions in relation to educational inclusion, the links that establish between NEE and inclusion, the recognition of other groups that are subject to exclusion and / or discrimination in school systems, the critical knots involved in the attention of some of these groups and the training possibilities offered by their institution in this field. Among the main findings are the expansion of inclusion ideas that, in the opinion of these academics, has resulted in concern for other groups subject to exclusion, not limited to the care of students with NEE. In addition, they conclude that the future teachers trained by the Universidad Católica del Maule, although they are sensitive to the subject, do not yet have sufficient competences to implement effective inclusive projects and tools to work with diverse school communities.